Estudo da atividade larvicida da Agave sisalana contra Aedes Aegypti - Nunes, Fabíola da Cruz (2013)
Dengue is a viral systemic disease caused by an arboviral of Flaviviridae family, affecting about a 100 million cases per year in Brazil. It is endemic in tropical regions such as Southeast Asia, South Pacific, East Africa, Caribbean and Latin America. The disease is transmitted by Aedes aegypti (Linnaeus, 1762), a mosquito that is the main target for the disease control through strategies ranging from the larval to the adult combat. The larvicides commonly used to combat the vector, besides being toxic, present drop in larvicide efficacy since the A. aegypti larvae has developed resistance to these products. Thus, the search for new active principles that are effective in combating the mosquito is required. In this sense, Agave sisalana is a plant that is produced in several states in the Brazilian northeast region, which is used in the sisal industry. Only 5% of the plant is recovered, and its residual liquid completely wasted. In this way, the aim of this research project was to investigate the larvicidal action of the juice of Agave sisalana against larvae of A. aegypti. In larvicidal activity assays, fourth stage A. aegypti larvae were used, exposed to different concentrations of A. sisalana liquid waste during 24 hours. After the larvicidal activity assays, it was possible to determine the LC50 that was 5.9 mg / mL. Next we explored the cytotoxic activity of A. sisalana in hemocytes of A. aegypti larvae through the flow cytometry. The experiments showed an increase of cellular necrosis after 12 hours of exposure of the larvae to submaximal concentrations of sisal liquid waste (7.4% in control group vs. 28.5% in the experimental group after 12 hours; 6.2% in the control group vs. 22.7% in the experimental group after 24 hours). The histological alterations were confirmed by histopathological analysis, which showed lyses of the mesentery epithelial cells of larvae as well as peritrophic membrane destruction. Furthermore, nitric oxide (NO) production by hemocytes, an important defense strategy of mosquitoes, was checked after 3, 6 and 24 hours of larvae exposure to the A. sisalana liquid waste. There was a reduction in NO levels of approximately 76.6% after 3 hours, 83% after 6 hours and 83.8% after 24 hours of exposure. In this way, the A. sisalana liquid waste constitutes an effective alternative and economically feasible for the dengue vector combat. The outcomes of our research resulted in the patent application for an insecticide against A. aegypti larvae.